Kaempferol Alleviates Oxidative Stress and Apoptosis Through Mitochondria-dependent Pathway During Lung Ischemia-Reperfusion Injury - Yang, Chunli; Yang, Wenkai; He, Zhaohui; Guo, Jinghua; Yang, Xiaogang; Wang, Rongsheng; Li, Hongbo (Frontiers in Pharmacology, 2021)
In previous study, we reported that kaempferol ameliorates significantly lung ischemia-reperfusion injury (LIRI), and may be achieved by targeting the SIRT 1 pathway. This study further explored the anti-LIRI mechanism of kaempferol. In vitro, the rat alveolar epithelial cells L2 was cultured and subjected to anoxia/reoxygenation (A/R) insult. In vivo, SD rats were operated to establish LIRI model. The related indicators of oxidative stress and apoptosis in L2 cells and rats lung tissues were detected. Results showed that kaempferol pre-treatment significantly increased the cell viability, improved mitochondrial membrane potential, inhibited the opening of mitochondrial permeability transition pores, reduced the levels of oxidative stress and apoptosis, increased the expressions of Bcl-2 and mitochondrial cytochrome c, and decreased the expressions of Bax and cytoplasmic cytochrome c in L2 cells after A/R insult. In vivo, kaempferol improved the pathological injury, inhibited the levels of oxidative stress and apoptosis, increased the expressions of Bcl-2 and mitochondrial cytochrome c, and decreased the expressions of Bax and cytoplasmic cytochrome c in rats lung tissues after I/R. However, the aforementioned effects of kaempferol were significantly attenuated by the SIRT 1 inhibitor EX527 or the PGC-1α inhibitor SR-18292. What’s more, SR-18292 has not reversed the effect of kaempferol on increasing the protein activity of SIRT 1. Above results suggest that kaempferol ameliorates LIRI by improving mitochondrial function, reducing oxidative stress and inhibiting cell apoptosis. Its molecular mechanism of action includes the SIRT 1/PGC-1α/mitochondria signaling pathway.